Comparison of muscular endurance training periodisation models with equated volume and intensity in adolescent hockey players at Bukit Jalil Sports School. - Ramalingam, Shankaralingam (2011)
The purpose of the present study was to determine of significant differences exist between two different models; linear periodisation (LP) and daily undulating periodisation (DUP); in elicting superior gains in muscular endurance for the back squat and bench press. Twenty (n=20) adolescent athletes between 16 to 17 years old underwent a 12 wk strength training programme. They were tested for the lowwer-body muscular endurance (70% of estimated 1RM bench press). Following initial testing participants were randomly assigned to one of the two training groups with ten partifcipants in each group. Participants performed the programmed exercises twice a week throught the training period with volume and intensity equated for both groups at the end of the experimental period. The LP group linearly changed intensity and volume over each 4 wk training phase while DUP group changed intensity and volume daily. Muscular endurance for back squat (LP=51.11%, DUP=61.60%) and bench press (LP=55.83%, DUP=48.48%) increased significantly from pre to post-test. However, there were two significant differences measured between groups. Therefore each of the two models proved effective in increasing back squat and bench press muscular endurance over the cource of 12 weeks.